Cell-in-cell phenomenon associates with aggressive characteristics and cancer-related mortality in early oral tongue cancer - Almangush A; Mäkitie AA; Hagström J; Haglund C; Kowalski LP; Nieminen P; Coletta RD; Salo T; Leivo I (BMC, 2025)
BackgroundCell-in-cell structures (caused by cell cannibalistic activity) have been related to prognosis of many cancers. This is the first multi-institutional study to assess the prognostic impact of cell-in-cell structures in a large cohort of early oral tongue squamous cell carcinomas (OTSCC).MethodsA total of 308 cases from five Finnish University Hospitals and from the A.C. Camargo Cancer Center, SAo Paulo, Brazil, were included in this study. Cell-in-cell structures were evaluated on surgical postoperative sections that stained with hematoxylin and eosin staining.ResultsWe found that cell-in-cell structures associated with cancer-related mortality in univariable analysis with a hazard ratio (HR) of 2.99 (95%CI 1.52-5.88; P=0.001). This association was confirmed in multivariable analysis (HR 2.22, 95%CI 1.12-4.44; P=0.024). In addition, statistically significant associations were observed between the cell-in-cell structures and other adverse histopathologic characteristics including deep invasion (P< 0.001), high index of tumor budding (P=0.007), worst pattern of invasion (P< 0.001), perineural invasion (P=0.01), and stroma-rich pattern (P=0.001).ConclusionsOur findings demonstrate a significant relationship between cell-in-cell formation and aggressive characteristics of early OTSCC. Cell-in-cell structures have a distinct impact as a novel prognostic indicator in early OTSCC and they can be easily assessed during routine pathology practice.